2022
DOI: 10.7554/elife.80859
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation resistance differences in Drosophila species can be largely explained by variations in cuticular hydrocarbons

Abstract: Maintaining water balance is a universal challenge for organisms living in terrestrial environments, especially for insects, which have essential roles in our ecosystem. Although the high surface area to volume ratio in insects makes them vulnerable to water loss, insects have evolved different levels of desiccation resistance to adapt to diverse environments. To withstand desiccation, insects use a lipid layer called cuticular hydrocarbons (CHCs) to reduce water evaporation from the body surface. It has long … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 85 publications
2
35
0
Order By: Relevance
“…Our experiments showed that transgenic D. melanogaster flies with Dmoj/mElo overexpression were significantly more desiccation resistant (Mean ± SE, Females: 13.0 ± 0.3 h, Males: 7.8 ± 0.2 h) compared to control flies (Females: 8.4 ± 0.2 h, Males: 5.9 ± 0.1 h) and flies with Dmel/mElo overexpression (Females: 10.3 ± 0.2 h, Males: 6.0 ± 0.2 h) ( Figure 2C ). This result demonstrated that the production of longer mbCHCs can significantly increase desiccation resistance, consistent with our previous findings using synthetic mbCHCs (Wang et al ., 2022).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Our experiments showed that transgenic D. melanogaster flies with Dmoj/mElo overexpression were significantly more desiccation resistant (Mean ± SE, Females: 13.0 ± 0.3 h, Males: 7.8 ± 0.2 h) compared to control flies (Females: 8.4 ± 0.2 h, Males: 5.9 ± 0.1 h) and flies with Dmel/mElo overexpression (Females: 10.3 ± 0.2 h, Males: 6.0 ± 0.2 h) ( Figure 2C ). This result demonstrated that the production of longer mbCHCs can significantly increase desiccation resistance, consistent with our previous findings using synthetic mbCHCs (Wang et al ., 2022).…”
Section: Resultssupporting
confidence: 93%
“…We had previously shown that the length of mbCHCs can largely explain desiccation resistance across Drosophila species (Wang et al, 2022). Drosophila species produces combinations of mbCHCs of different carbon backbone lengths ranging from 24 carbons (2MeC24) to 32 carbons (2MeC32) (Jallon and David, 1987; Khallaf et al, 2021; Wang et al ., 2022). D. melanogaster mainly produces 2MeC24, 2MeC26, and 2MeC28, while D. mojavensis produces longer mbCHCs, 2MeC28, 2MeC30, and 2MeC32 ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations